Development and Validation of a New Risk Prediction Score for Life-Threatening Ventricular Tachyarrhythmias in Laminopathies - Wahbi, Karim; Ben Yaou, Rabah; Gandjbakhch, Estelle; Anselme, Frédéric; Gossios, Thomas; Lakdawala, Neal K.; Stalens, Caroline; Sacher, Frédéric; Babuty, Dominique; Trochu, Jean-Noel; Moubarak, Ghassan; Savvatis, Kostantinos; et al. (Circulation (New York, N.Y.), 2019)
BACKGROUND:An accurate estimation of the risk of life-threatening (LT) ventricular tachyarrhythmia (VTA) in patients with LMNA mutations is crucial to select candidates for implantable cardioverter-defibrillator implantation. METHODS:We included 839 adult patients with LMNA mutations, including 660 from a French nationwide registry in the development sample, and 179 from other countries, referred to 5 tertiary centers for cardiomyopathies, in the validation sample. LTVTA was defined as (1) sudden cardiac death or (2) implantable cardioverter defibrillator–treated or hemodynamically unstable VTA. The prognostic model was derived using the Fine-Gray regression model. The net reclassification was compared with current clinical practice guidelines. The results are presented as means (SD) or medians [interquartile range]. RESULTS:We included 444 patients, 40.6 (14.1) years of age, in the derivation sample and 145 patients, 38.2 (15.0) years, in the validation sample, of whom 86 (19.3%) and 34 (23.4%) experienced LTVTA over 3.6 [1.0–7.2] and 5.1 [2.0–9.3] years of follow-up, respectively. Predictors of LTVTA in the derivation sample weremale sex, nonmissense LMNA mutation, first degree and higher atrioventricular block, nonsustained ventricular tachycardia, and left ventricular ejection fraction (https://lmna-risk-vta.fr). In the derivation sample, C-index (95% CI) of the model was 0.776 (0.711–0.842), and the calibration slope 0.827. In the external validation sample, the C-index was 0.800 (0.642–0.959), and the calibration slope was 1.082 (95% CI, 0.643–1.522). A 5-year estimated risk threshold ≥7% predicted 96.2% of LTVTA and net reclassified 28.8% of patients with LTVTA in comparison with the guidelines-based approach. CONCLUSIONS:In comparison with the current standard of care, this risk prediction model for LTVTA in laminopathies significantly facilitated the choice of candidates for implantable cardioverter defibrillators. CLINICAL TRIAL REGISTRATION:URLhttps://www.clinicaltrials.gov. Unique identifierNCT03058185.